Extranasopharyngeal angiofibroma originating from sphenoid sinus: a case report - San, Turhan; Tekin, Muhammet; Halit Çam, Osman; Kılıçaslan, Adem; Zemheri, Ebru (ENT Updates, 2012)
Angiofibromas typically arise from the nasopharynx in young adolescent males. Extranasopharyngeal angiofibroma (ENA) implicates the vascular fibrous nodules occurring outside the nasopharynx. Since the clinical characteristics of ENA differ from those of nasopharyngeal angiofibroma, diagnosis can be challenging. Biopsy is usually discouraged due to the risk of bleeding. A high index of suspicion and a methodical evaluation are essential in establishing the proper diagnosis and treatment. We report the rare case of a 49-year-old woman who presented with headache and epistaxis. The mass was found to arise from right sphenoid sinus and total excision could be accomplished with endoscopic sinus surgery. Postoperative histopathologic analysis was consistent with an angiofibroma. To the best of our knowledge, only 3 cases of ENA arising from the sphenoid sinus have been previously reported in the English-language literature.